Antroquinonol Lowers Brain Amyloid-β Levels and Improves Spatial Learning and Memory in a Transgenic Mouse Model of Alzheimer’s Disease - Chang, Wen-Han (Sci Rep, 2015)
Alzheimer’s disease (AD) is the most common form of dementia. The deposition of brain amyloid-β peptides (Aβ), which are cleaved from amyloid precursor protein (APP), is one of the pathological hallmarks of AD. Aβ-induced oxidative stress and neuroinflammation play important roles in the pathogenesis of AD. Antroquinonol, a ubiquinone derivative isolated from Antrodia camphorata, has been shown to reduce oxidative stress and inflammatory cytokines via activating the nuclear transcription factor erythroid-2-related factor 2 (Nrf2) pathway, which is downregulated in AD. Therefore, we examined whether antroquinonol could improve AD-like pathological and behavioral deficits in the APP transgenic mouse model. We found that antroquinonol was able to cross the blood-brain barrier and had no adverse effects via oral intake. Two months of antroquinonol consumption improved learning and memory in the Morris water maze test, reduced hippocampal Aβ levels, and reduced the degree of astrogliosis. These effects may be mediated through the increase of Nrf2 and the decrease of histone deacetylase 2 (HDAC2) levels. These findings suggest that antroquinonol could have beneficial effects on AD-like deficits in APP transgenic mouse.